PENGARUH MOTIVASI KERJA DAN PENEMPATAN KARYAWAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN (STUDI PADA ANALIS KREDIT PT. BPD BALI CABANG UTAMA DENPASAR) - Binda Karmita, Sagung; Supartha, I Wayan Gede; Saroyini Priantini, Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Work motivation and staff positioning is one of the important issue that need to be taken into account by a management, in order to improve workplace satisfaction rating. Workplace satisfaction and employee performance begins from the appropriate work placement of individual employee, based on interest, talent and followed by motivation from management and their colleague. The purpose of this research is to analyze the influence of work place motivation and work placement to the overall satisfaction and performance of the staff in general. The research use 36 individuals as samples and all of them work inside the credit analysis at the BPD Bali (Regional development bank) of Bali, at their denpasar’s branch office. The method analysis use for it is PLS (partial least square). Variable that we look upon in this research is work motivation, work placement, overall satisfaction and work performance. The final result suggest there is a strongeffect work motivation to work satisfaction. Followed by, appropriate work placement with overall employee satisfaction. Other variable work motivation has positive and significant effect towards the employee performance. Then, appropriate work placement has direct positive effect towards improvement of the work performance. And higher work satisfaction improved the work performance We recommending the company to focus upon the right work placement, because with the right work placement that take into consideration the staff interest and talent, it will create positive effect towards their satisfaction and performance. An employee will able to provide better outcome in their day to day work, if the conditions of right work placement based on talent and skill is fulfilled.
Keywords: Work motivation, work placement, staff work satisfaction and performance.